Inhaled corticosteroids use in childhood respiratory diseases: an italian survey on pediatricians' prescription habits - Giovanni Cerimoniale; Paolo Becherucci; Maria Carmen Verga; Giuseppe Di Mauro; Luciana Indinnimeo; Alberto Villani; Mariangela Tosca; Gian Luigi Marseglia; Marzia Duse; Paolo Biasci; Mattia Doria; Diego Peroni; et al. (BMC, 2021)
Abstract Background A national consensus document on inhaled corticosteroids (ICS) use in childhood, produced by the main Italian pediatric scientific societies, has been recently released. The aim of this study was to gather information on the current pediatricians' ICS prescription habits in Italy for the management of the most common pediatric respiratory diseases, namely allergic rhinitis (AR), asthma, preschool wheezing and laryngitis. Methods From the 1st October 2018 to the 31st January 2019 a link to an online questionnaire was sent monthly through a newsletter to the members of the Italian Society of Pediatrics. The questionnaire included 18 items on ICS use in the most common pediatric respiratory diseases. Data collection and reporting was based on STROBE Statement Checklist for cross-sectional studies. Results One thousand-two questionnaires were returned from primary care pediatricians (39.1%), hospital pediatricians (38.7%), private practicers (16.4%), university pediatricians (3.1%) and Pediatrics residents (2.7%). We found a good adherence to the international guidelines on AR, with prevalent use of oral antihistamine (60.6%) in the secretive phenotype and nasal ICS in the obstructive phenotype (64.8%). In asthma exacerbations ICS are not used in 53.4% of cases, but they are used at high dose in 27.9% and at low dose in 18.7% of cases. In intermittent asthma, ICS are not chosen as a daily controller therapy in 54.1% of cases, while they are chosen as a low dose daily therapy in 44.5% of cases (high dose in 1.4%). In children with persistent asthma, ICS are chosen as a daily low dose therapy in 67.4% of cases and as a daily high dose therapy in 31%. In the management of preschool wheezing, when a long-term treatment is needed, ICS are chosen both alone and in association with antileukotrienes in 71.4% of cases. Children affected by recurrent asthma exacerbations and wheezing are closely followed up, in particular by their primary care pediatricians. The preference for certain molecules in the treatment of different respiratory diseases also emerged. Conclusions Pediatricians' ICS prescription habits in Italy should be improved, especially in the management of asthma. Future surveys on a more numerous sample will be useful to analyze differences in prescription habits on the basis of pediatricians' work settings and geographical distribution.